Posterior deltoid shoulder tightness: shoulder pain risk factors in swimmers - Matsuura, Y.; Fujimoto, T.; Mise, T.; Edama, M.; Shimoyama, Y. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Shoulder pain is the most common complaint in swimming. Muscle stiffness in the posterior shoulder is associated with shoulder pain in overhead sports(Myers et al., 2006). However, this relationship is unclear in swimmers. This muscle stiffness can be measured as the shear elastic modulus using ultrasonic shear wave elastography (SWE). The purpose of this study was to investigate and identify risk factors for shoulder pain in swimmers based on elastic muscle coefficient by SWE, joint range of motion, and isometric muscle strength. METHODS Forty-eight competitive swimmers (18-28 years; 29 males) were followed up for 6 months. Baseline measurements of the elastic modulus of the pectoralis minor, supraspinatus, infraspinatus, posterior deltoid, and pectoralis minor muscles were obtained using shear wave elastography. Range of motion and isometric strength were measured using a goniometer and a handheld dynamometer, respectively. The questionnaire was administered weekly to determine shoulder pain occurrence over 6 months. Additionally, differences between shoulders with and without pain were investigated using the Mann-Whitney U test. Logistic regression analysis and recipient operating characteristic curves identified the risk factors.